How to Implement Effective Prediction and Forwarding for Fusable Dynamic Multicore Architectures - Robatmili, Behnam; Li, Dong; Esmaeilzadeh, Hadi; Govindan, Sibi; Smith, Aaron; Putnam, Andrew; Burger, Doug; Keckler, Stephen (19th IEEE International Symposium on High Performance Computer Architecture (HPCA), 2013)
Dynamic multicore architectures, that fuse and split cores at run time, potentially offer a level of performance/energy agility that static multicore designs cannot achieve. Conventional ISAs, however, have scalability limits to fusion. EDGE-based designs offer greater scalability but to date have been performance limited by signiﬁcant microarchitectural bottlenecks. This paper addresses these issues and makes three major contributions. First, it proposes Iterative Path Prediction to address low next block prediction accuracy and low speculation rates. It achieves close to taken/not-taken prediction accuracy for multi-exit instruction blocks while also speculating the predicated execution path within the block. Second, the paper proposes Exposed Operand Broadcasts to address the overhead of operand delivery for high fanout instructions by exposing a small number of broadcast operands in the ISA. Third, we present a scalable composable architecture called T3 that uses these mechanisms and show it can operate across a wide range of power and performance spectrum by increasing energy efﬁciency and performance signiﬁcantly. Compared to previous EDGE designs, T3 improves energy efﬁciency by about 2x and performance by up to 50%.